Pathophysiological role of fatty acid‐binding protein 4 in Asian patients with heart failure and preserved ejection fraction - Tomonari Harada (ESC Heart Failure, 2020)
Abstract Aims Systemic metabolic impairment is the key pathophysiology of heart failure (HF) with preserved ejection fraction (HFpEF). Fatty acid‐binding protein 4 (FABP4) is highly expressed in adipocytes and secreted in response to lipolytic signals. We hypothesized that circulating FABP4 levels would be elevated in patients with HFpEF, would correlate with cardiac structural and functional abnormalities, and could predict clinical outcomes. Methods and results Serum FABP4 measurements and echocardiography were performed in patients with HFpEF (n = 92) and those with coronary artery disease free of HF (n = 20). Patients were prospectively followed‐up for a composite endpoint of all‐cause mortality or HF hospitalization. Compared with patients with coronary artery disease, those with HFpEF had higher FABP4 levels [12.5 (9.1–21.0) vs. 43.5 (24.6–77.4) ng/mL, P < 0.0001]. FABP4 levels were associated with cardiac remodelling (left ventricular mass index: r = 0.29, P = 0.002; left atrial volume index: r = 0.40, P < 0.0001), left ventricular systolic and diastolic dysfunction (global longitudinal strain: r = −0.24, P = 0.01; E/e′ ratio: r = 0.29, P = 0.002; and N‐terminal pro‐B‐type natriuretic peptide: r = 0.62, P < 0.0001), and right ventricular dysfunction (tricuspid annular plane systolic excursion: r = −0.43, P < 0.0001). During a median follow‐up of 9.1 months, there were 28 primary endpoints in the HFpEF cohort. Event‐free survival was significantly decreased in patients with FABP4 levels ≥43.5 ng/mL than in those with FABP4 levels <43.5 ng/mL (P = 0.003). Conclusions Serum FABP4 levels were increased in HFpEF and were associated with cardiac remodelling and dysfunction, and poor outcomes. Thus, FABP4 could be a potential biomarker in the complex pathophysiology of HFpEF.